Performance analysis and experimental investigation on mechanical properties of RCC beam with fibre wrapping. (2023) - Mohana Sundari, S.; Vigneshkannan, S.; Kannan, C.; Rangaraj, A.; Amutha, M.; Prakhash, N.; Lingeshwaran, N.
Abstract: In recent years the usage of fibres for construction works has been developed rapidly due to its high strength and high performance. In the current research work of Kevlar, kenaf the basalt fibre of strengthening of flexure beam in bending test by reinforced concrete beam in different groups. The ultimate load and deflection of flexural strengthening effect on the behavior of externally bonded of RC beams with Kevlar kenaf, basalt fibres, wrapped in single layer of U-configuration, partial wrapping technique. The results showed that Kevlar, kenaf, basalt fibre wrapping of RC beams by increasing the flexural strength of 42%, 40% and 40% with full wrapping technique and 34%, 33.25% and 37% respectively with partial wrapping technique. This concept can be highly implemented in repair and rehabilitation work and in the environmentally affected zone.